A Trustworthy Biological Assets Governance System Using Decentralized Identity - Fang, Zhengkang; Yu, Jing; Fang, Shufen; Wang, Shuo; Chan, Weilin; Gao, Zexin; Gai, Keke (IEEE International Conference on Cyber Security and Cloud Computing (CSCloud) (Online), 2024)
Along with the development of the biological industry, the system of biological assets governance has a higher-level requirement in asset identity verification due to the demands of digitization and Financial Technology (FinTech). In order to achieve broad scalability and adaptability in the governance of biological assets' identities, this work proposes a Biological Assets Decentralized Identity Management (BA-DID) system that develops a Decentralized Identity (DID)-based solution to addressing the verification issues in biological assets while considering multi-dimensional requirements. Blockchain technology is the fundamental infrastructure of the system. Authenticated certificates of the asset owners verify identity attributes. Financial Service Institutions (FSI) and governance agencies act as issuers, providing Verifiable Credentials (VC) for biological assets by using a group of attributes over a consensus. The asset owners hold VCs and can be available to other organizations as proof of the corresponding asset attributes. Our evaluations have demonstrated that the proposed approach has superior performance in biological assets verification, security, and maintenance.